Institutional Ensuring of Economic Security of the State in Terms of Globalization - IMAMOV, Marsel M. (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
The article presents a retrospective analysis of methodological approaches to evaluating the level of economic security of the country that allowed to make conclusions about the variety of economic indicators used in the evaluating the economic security, about the impossibility of use of single integrated indicator for different countries of the world in connection with their definite national interests, the importance of the investment process as the main factor in determining the quantitative threat to the economic security of national economy, the priority of mathematical methods in evaluating the level of economic security, about the importance of the investment process as the main factor in determining the quantitative threat to the economic security of national economy, about the priority of mathematical methods in evaluating the level of economic security and about the necessity of complex application of methods of evaluation of economic safety of national economy with the aim of improving the level of its forecasting and warning of economic threats. The practical aiming of the article is determined by the possibilities in the formation of complex solutions that are identified in the legal documents that can be presented in order to stabilize the economic environment of the state.